STUDY OF PANDAWA CHARACTERS IN MAHABHARATA'S STORY LEARNED WITH INDONESIAN CHARACTER EDUCATION - Arifin, Muhammad; Hakim, Arif Rahman (CV ODIS, 2021)
Wayang has been recognized by UNESCO as a Masterpiece of Oral and Intangible Heritage of Humanity. However, in reality, there are facts among the younger generation of Indonesians who are still low on an understanding of Wayang culture, especially in the Mahabharata story. Specifically, it is often found that the young generation in formal education circles understands the character of the Pandawa characters in the Mahabharata story. On the other hand, the younger generation of Indonesia is also being encouraged to have a character that is following the character education program of the Indonesian nation. This article, which is compiled in the form of a literature review, aims to examine the character of the Pandawa figures in the Mahabharata story to be aligned with the character education of the Indonesian nation in the formal education environment. The conceptual substance of this article is in the form of an effort to optimize character education through understanding the Pandawa characters in the Mahabharata story so that it can form the younger generation as human resources who have superior competencies as well as holistic characteristics as a manifestation of building the civilization of the life of the nation and state of Indonesia.